Research Trends in Studio Pedagogy and their Impact on Design Learning Outcomes: A Bibliometric Study - Bt samsuddin, Yati; Purnama, Andry Priyadharmadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to map research trends on studio pedagogy/Studio-Based Learning (SBL) and its linkage to design learning outcomes in the context of Visual Communication Design (VCD) using a bibliometric approach. Data were retrieved from Google Scholar via Publish or Perish (PoP) and visualized with VOSviewer to identify term co-occurrence patterns and thematic clusters. The PoP summary displayed at this stage indicates a corpus consisting of one document (publication year 2015–2025) with 7,980 citations and an h-index of 1, which is insufficient to represent longitudinal publication trends. VOSviewer visualizations (density, network, and overlay) show a dominant “sbl” node strongly associated with “sparse bayesian learning” and other technical terms, indicating acronym ambiguity that introduces cross-domain contamination into the dataset. Nonetheless, the maps also reveal a design-education cluster connecting “studio,” “design education,” “teaching,” and “course,” suggesting that part of the corpus is relevant to studio pedagogy. Overall, the findings highlight that valid bibliometric mapping of VCD studio pedagogy depends on precise query construction (using full phrases rather than acronyms) and rigorous data cleaning/term normalization. Future work should refine search queries and apply thesaurus-based filtering to capture VCD-specific themes, including digital/hybrid studios, outcome-based assessment, and feedback mechanisms.